Exploring Factors Influencing Students’ Engagement in Deep Learning-Based EFL Speaking - Aqidatul Izzah Syafruddin; Nurdevi Bte Abdul; Hasnawati Latif (Journal of English Language and Education, 2026)
Student engagement is essential for fostering significant learning and enhancing speaking proficiency in EFL lessons. While prior research has investigated student involvement and deep learning independently, there is a paucity of studies addressing the elements that affect students' participation in deep learning-oriented EFL speaking activities, especially at the junior high school level. This study defines deep learning-based EFL speaking activities as speaking tasks that foster meaningful comprehension, critical analysis, cooperation, reflection, and the application of information through genuine communication. This study sought to examine the factors affecting students' engagement in these learning activities. The study utilized a descriptive qualitative approach and featured 10 eighth-grade students from SMP Muhammadiyah Lajoa, recruited via purposive sampling. Data were gathered via classroom observations and semi-structured interviews, subsequently analyzed employing the interactive model proposed by Miles, Huberman, and Saldaña (2014). The results identified five elements affecting student engagement: teaching strategy, individual motivation, student-teacher relationship, students’ English proficiency and teaching facilities. The data suggest that student involvement is influenced by the interplay of internal and external influences. The study emphasizes the significance of establishing supportive, engaging, and student-centered learning settings to promote meaningful engagement and active participation in EFL speaking activities.